2014
DOI: 10.1016/j.bbadis.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Both hydrogen peroxide and transforming growth factor beta 1 contribute to endothelial Nox4 mediated angiogenesis in endothelial Nox4 transgenic mouse lines

Abstract: Vascular endothelial cells (ECs) are responsible for post-ischemic angiogenesis, a process that is regulated by reactive oxygen species. Recent studies indicate that endothelial Nox4 based NADPH oxidase may have a key role. This study examines the role of endothelial Nox4 in ischemia-induced angiogenesis and explores the potential mechanisms involved. Mouse lines overexpressing human Nox4 wild type (EWT) or its dominant negative form P437H (EDN) specifically in the endothelium were used. Non-transgenic litterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 32 publications
3
58
0
Order By: Relevance
“…DDAH‐2 plays a crucial role in regulating ADMA metabolism of ECs 24, 25. We analyzed whether overexpression of DDAH‐2 protects against ADMA‐induced impairment of simvastatin‐mediated NO production and tube formation.…”
Section: Resultsmentioning
confidence: 99%
“…DDAH‐2 plays a crucial role in regulating ADMA metabolism of ECs 24, 25. We analyzed whether overexpression of DDAH‐2 protects against ADMA‐induced impairment of simvastatin‐mediated NO production and tube formation.…”
Section: Resultsmentioning
confidence: 99%
“…NOX4 enhances angiogenesis under ischemic conditions and is therefore protective against ischemic injury in lower limbs (35). Furthermore, Chen et al demonstrated that endothelial NOX4 mediates angiogenesis (36). Thus, the presence of NOX4 in endothelial cells may induce a difference in phenotype between cardiac-specific NOX4 KO mice and systemic NOX4 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may have caused the disparity in results. Angiogenesis is induced not only by VEGF but also by the platelet-derived growth factor [25] and transforming growth factor beta [26] . Cilostazol inhibits the activity of phosphodiesterase type 3 [27] , leading to the upregulation of the hepatocyte growth factor [28] and possible induction of angiogenesis [29] .…”
Section: Discussionmentioning
confidence: 99%